2022
DOI: 10.1007/s11883-022-00987-y
|View full text |Cite
|
Sign up to set email alerts
|

A Nutrigenetic Update on CETP Gene–Diet Interactions on Lipid-Related Outcomes

Abstract: Purpose of Review An abnormal lipid profile is considered a main risk factor for cardiovascular diseases and evidence suggests that single nucleotide polymorphisms (SNPs) in the cholesteryl ester transfer protein (CETP) gene contribute to variations in lipid levels in response to dietary intake. The objective of this review was to identify and discuss nutrigenetic studies assessing the interactions between CETP SNPs and dietary factors on blood lipids. Recent Findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 110 publications
0
10
1
1
Order By: Relevance
“…Individually, the SNPs in our study did not show any significant interaction with dietary factors. The discrepancies in findings between our study and others could be because of allele frequencies and effect sizes which differ between populations [1,32]. Another plausible explanation is differences in dietary pattern and the methods used to assess dietary intake [1].…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…Individually, the SNPs in our study did not show any significant interaction with dietary factors. The discrepancies in findings between our study and others could be because of allele frequencies and effect sizes which differ between populations [1,32]. Another plausible explanation is differences in dietary pattern and the methods used to assess dietary intake [1].…”
Section: Discussioncontrasting
confidence: 85%
“…Abnormalities in lipid metabolism have been linked to the development of obesity [16,58]. We used a nutrigenetic approach to see if dietary intake can modify this link by employing a GRS from the two lipid pathway genes, CETP and LPL, which have been shown to have the strongest effect on lipid concentrations [21,24,25,[27][28][29]32,59]. To account for the effect of T2D on lipid levels, we adjusted for T2D status, anti-diabetic medication, and duration of T2D in our analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In observational studies, significant interactions between diet and rs3764261 have been described. For example, in a study of 4,700 Iranian participants, a correlation between higher fish intake and a decrease in total cholesterol in individuals carrying the A allele was found ( 35 ). The frequency of the C allele in the Latin American population is 0.66, whereas for the A allele is 0.34 ( 20 , 21 ).…”
Section: Genetics In Obesity In the Latin American Populationmentioning
confidence: 99%
“…Genome-wide association studies have identified several genetic loci associated with cardiometabolic traits but most of these studies have been performed in Caucasian populations (10)(11)(12)(13)(14)(15). Similarly, majority of nutrigenetic studies have been performed in Western countries and the findings might not be applicable to low-income countries due to variations in allele frequencies, dietary pattern, and environmental factors (5,16).…”
Section: Introductionmentioning
confidence: 99%